The Role of Administrative Management in Managing Human Resources Management Practices in the Salah Al- Din Electricity Distribution Branch From an Administrative Point of View (Case Study) - Mohammed Faraj Abdullah; Salah Ne'meh Jawad (Indonesian Journal of Public Administration Review, 2026)
The objective of this research is to investigate the relationship that exists between e-management and improvement on human resource management (HRM) practices with in Salah al-Din Electricity Distribution Company. The study specifically examines the effects of e-management on different aspects of HRM such as job analysis, recruitment, training and development, performance appraisal and reward. Research design: descriptive-analytical, data collection and sampling were companies of 250 employees who using questionnaires and analysis. The study employs correlation and regression analysis to gauge the impact of e- management instruments, such as e-training, digital communication network and electronic governance on better HRM practices. Results reveal a significantly strong positive relationship between e-management and HRM practices such as e-recruitment (r=.50), performance appraisal (r=0.50) and training of employee r=0.57). However, the study also highlights weaknesses in e- monitoring mechanisms, suggesting the need for further improvements in electronic supervision and administrative efficiency. These findings emphasize the importance of digital transformation in HRM, recommending the adoption of AI-driven recruitment systems, enhanced digital monitoring, and expanded e-learning platforms to optimize human resource management in the organization